Sizing software of a solar farm system / Nuril Yaqin Rahim - Rahim, Nuril Yaqin (2013)
This paper presents sizing software for the design of a solar farm system. A solar farm is basically a large-scale application of grid-connected photovoltaic system installation. Therefore this software is created to simplify the numerous calculations for the sizing method. The sizing software provides few guidelines to the designer for the planning procedure before the final of optimum array configuration is decided. Some specifications that the designer may consider are the type of PV module, the type of inverter, the available space for installation, the required energy per year and also the sum of money to be allocated for the instalment. The output result of this software will be the suggestion of possible configuration of the total number of modules in series per string with the total number of strings in parallel. This software also does the prediction of the system performances such as final yield, specific yield and performance ratio. The expected income is provided by the software is based on the Feed-in Tariff rates and the energy generated by the system. The software used in the design is Visual Basic where it consists of programming and windows application design.